Interpretation of loga statues in Bada Valley culture: an interpretive anthropology study - Yudhanto, Sigied Himawan; Prayoga, Dedy Eka Timbul (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
This study analyzes the symbolic meaning of Loga statues in the Bada Valley through the interpretive, symbolic anthropology approach of Clifford Geertz and the symbolic interpretation of Victor Turner. Using Geertz's theory, the perspective views Loga statues as cultural "texts" that reflect the worldview, values, and local identity of the Bada community. Turner's perspective views Loga statues with an emphasis on the role of statues in the context of rituals as symbols of social structure and community solidarity. The research method uses qualitative descriptive methods with an ethnographic basis; the research location is in Pada village, Bada Valley, Lore Lindu National Park, Central Sulawesi, and data collection methods are obtained through observation and in-depth interviews. The results of the study show that Loga statues function as symbols that connect people with their ancestors, maintain and strengthen social ties, and reproduce cultural values ​​through rituals. The combination of these two theories provides a comprehensive insight into how the symbols in Loga statues play a role in maintaining cultural sustainability and strengthening the identity of the Bada community. Loga statues are not only artifacts but also active agents in the social and spiritual life of the people in the Bada Valley.